"Sahabat Ibu Balita" Program to Improve Mothers Knowledge and Skills in Monitoring The Growth of Infants Aged 0-6 Months - Rohmah, Miftakhur (Health Notions, 2017)
The first 6 months of infant life is a golden opportunity for early detection, as well as a growth assessment. Special forms of growth and development are stimulation. Stimulation should be done routinely, continuously at every opportunity and in all infants and toddlers. Based on the fact that there are many mothers who do not know how to perform good stimulation and unskilled in stimulating the result is still found the existence of parents who do not provide stimulation of the baby with routine. The purpose of this study was to determine "differences in mothers knowledge and skills in monitoring of growth and development infants aged 0-6 months among mothers who applied âSahabat Ibu Balitaâ and those who did not apply  the âSahabat Ibu Balitaâ. The design of this research was quasi-experiment with pre-posttest with control group. The samples used were parents who had babies aged 0-6 months in the work area of ââBabakansari Community Health Center. Sample size was 66, then divided into 2 groups that was intervention group and control group. They were selected by  multistage sampling and executed in December 2016 to January 2017. Result of research by Chi square test there was a significant difference of intervention group and control group on the knowledge and skills. The application of âSahabat Ibu Balitaâ as a strategy to support the use of âKIA bookâ for mothers knowledge and skill in monitoring the growth and development was more optimal.